Quantum wave packet study of Li+H2+ inelastic scattering - Bulut, N; Gogtas, F; Akpinar, S (Elsevier, 2005)
Time dependent quantum wave packet calculations have been carried for the astrophysically important Li + H-2(+) collision process. The state-to-state and state-to-all inelastic probabilities for the entitled collision have been calculated. Sharp resonance features are observed in all transition probabilities at low collision energies. J-shifting approximation has been employed to estimate the inelastic integral cross-sections. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Dynamics; Chemistry; Accurate; Surface